Counseling for opioids prescribed at discharge of hospitalized adolescent trauma patients - Michael J. Mello; Lois K. Lee; Emily Christison-Lagay; Anthony Spirito; Sara Becker; Julie Bromberg; Stephanie Ruest; Mark R. Zonfrillo; Kelli Scott; Charles Pruitt; Karla Lawson; Isam Nasr; et al. (BMC, 2023)
Abstract Background Expert consensus recommends prescription opioid safety counseling be provided when prescribing an opioid. This may be especially important for youth with preexistent alcohol and other drug (AOD) use who are at higher risk of developing opioid use disorder. This study examined the frequency that adolescent trauma patients prescribed opioids at hospital discharge received counseling and if this differed by adolescents' AOD use. Method This study was embedded within a larger prospective stepped-wedge type III hybrid implementation study of AOD screening across a national cohort of pediatric trauma centers. Data were collected during 2018-2021 from admitted adolescent trauma patients (12-17 yo) at seven centers. Patient data were extracted from the electronic health record (EHR) on any prescribed discharged opioids, documentation of counseling delivered on prescribed opioid, who delivered counseling, and patients' AOD screening results. Additionally, adolescents received an online survey within 30 days of hospital discharge that included asking about hospital discussions on safe use of prescription pain medication. Results Of the 247 adolescent trauma patients enrolled, 158 completed the 30-day survey. AOD screening results were documented in the EHR for 139 patients (88%), with 69 (44.1%) screening AOD-positive. Opioids at discharge were prescribed to 86 (54.4%) adolescent patients, with no significant difference between those screened AOD-positive and AOD-negative (42.4% vs. 46.3%, p = 0.89). Counseling was documented in the EHR for 30 (34.9%) of those prescribed an opioid and was not significantly different by sex, age, race, ethnicity or between adolescent patients with documentation of AOD use (29.3%) versus those who did not (33.3%, p = 0.71). According to the adolescent survey, among those prescribed an opioid, 61.2% reported someone had talked with them about safe use of newly prescribed pain medications with again no difference between AOD-positive and AOD-negative screening results (p = 0.34). Conclusions Although adolescent trauma patients recalled discussions on safe use of prescribed pain medication more often than was documented in the EHR, these discussions were not universal and did not differ if adolescents had screened positive or negative for AOD use as documented in the EHR. Trial Registry: clinicaltrials.gov NCT03297060.